Additional comments to the article written by Eymard Torres-Rodriguez et al: Reduction of cardiovascular risk in obese patients who participated in a lifestyle medicine program - John C. Longa López (Revista de la Facultad de Medicina Humana, 2022)
Dear Editor Chronic diseases have occupied a leading place in global morbidity and mortality statistics, given the increase in life expectancy and access to new therapeutic technologies and advanced drugs. Cardio-metabolic diseases such as diabetes, high blood pressure, dyslipidemia, and obesity, among others, are clear examples of both the impact and the advent of new therapeutic opportunities. In this study, the effect of a lifestyle program on the cardiovascular risk of enrolled patients was evaluated.